External noise suppression by intrinsic noise in a neuron - Tao Shen; Zhangcai Long; Bo Chen (Results in Physics, 2019)
Noises are usually being considered as a detrimental factor in signal processing. The usual method to deal with noise and enhance output signal is reducing noises from different sources. In this research, we demonstrated in a neuronal model that noise in output of a neuron driven by signal with external noise can be suppressed by internal noise of the neuron. This work revealed a new positive role of noise in noisy signal processing. Keywords: Noise, Neuron, Signal transmission